Biology and Management of Aphids in Sustainable Field Production of Cucurbits - Oscar E. Liburd; Teresia W. Nyoike (EDIS, 2008)
ENY-847, a 3-page illustrated factsheet by O. E. Liburd and T. W. Nyoike, provides information about aphids, their biology and lifecycle, damage, monitoring and management strategies for sustainable agriculture. Includes references. Published by UF Department of Entomology and Nematology, January 2008.